Determinants of fine-scale spatial genetic structure in three co-occurring rain forest canopy trees in Borneo - Kettle, Chris J.; Hollingsworth, Peter M.; Burslem, David F.R.P.; Maycock, Colin R.; Khoo, Eyen; Ghazoul, Jaboury (Perspectives in plant ecology, evolution and systematics, 2011)
Fine-scale spatial genetic structure (FSGS) within plant populations is an emergent property of the recruited adult trees, influenced by pollen and seed mediated gene flow, selection and demographic processes. This study aims to increase our understanding of the individual species traits that contribute to the generation of FSGS in the Dipteropcarpaceae, which is an ecologically and economically important family of tropical trees that dominate lowland forests in Southeast Asia. We examined FSGS in three co-occurring dipterocarp species at a single site in Borneo. Shorea xanthophylla, Parashorea tomentella and Dipterocarpus grandiflorus share limited seed dispersal but differ markedly in flower size, pollinator body size and pollen dispersal. Here we explore the role of pollen dispersal limitation in shaping FSGS in these three species. Using six microsatellite loci, we explore patterns of FSGS and landscape genetic structure and compare these across species. Significant FSGS was observed in S. xanthophylla and P. tomentella, both of which are known to have relatively limited pollen dispersal, but no clear signal of FSGS was observed in D. grandiflorus. Significantly greater FSGS was observed in P. tomentella ( Sp = 0.012) than S. xanthophylla ( Sp = 0.007) despite greater pollen dispersal in P. tomentella. Bayesian clustering analysis revealed significant structure in P. tomentella at the scale of the forest reserve (4000 ha). We discuss the alternative explanations for the observed patterns of FSGS emphasising the complexity of the mechanisms that can generate FSGS in long-lived trees. The extent of species-specific pollen dispersal is one factor that can contribute to differences in FSGS across species, but is not the only determinant. The observed patterns of FSGS and landscape scale genetic structure in S. xanthophylla and P. tomentella illustrate the potential of gap regeneration to counter act pollen dispersal and contribute to increased aggregation of related individuals (FSGS).